Al-Baqoroh Ayat 29 sebagai Kaidah al-Masyaqqoh at-Tajlibu al Taisir ( Studi Fenomena Kenaikan Harga Bahan Bakar Minyak ) - Hendri, Jul; Mahdi, Imam; Iqbal, Moch. (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstracts: The phenomenon of increasing fuel oil (BBM) prices in Indonesia occurred after the government itself agreed to a policy taking into account several reasons. This does not happen because there is no underlying cause, seeing that the greater the difference between the real market price and the retail price of subsidized fuel will certainly burden the state budget. If it is not addressed, the State Revenue and Expenditure Budget (APBN) will collapse. The increase in basic commodities also occurred in addition to the increase in fuel prices, giving rise to new problems for people in Indonesia, especially in the economy. However, the government should not remain silent watching what is happening in this country, they should continue to try to find steps to solve the problems that occur in society as a result of the increase in fuel prices. In this matter, the qaidah Al-masyaqqoh at-tajlibu al taisir (difficulty causes ease or difficulty brings ease) is a serious consideration for the government in making the right decision to eliminate the difficulties or difficulties that occur in this country by looking at the things that arise due to the increase in fuel prices itself which has negative and positive impacts on the country and the people within it.Keywords: Fuel Oil (BBM), Increase in basic commodities, Al-masyaqqoh at-tajlibu al taisir. Abstrak : Fenomena kenaikan harga Bahan Bakar Minyak (BBM ) di Indonesia terjadi setelah disepakatinya kebijakan dari pemerintah sendiri dengan mempertimbangankan beberapa sebab. Hal tersebut terjadi bukan karena tidak adanya sebab yang mendasarinya, melihat bahwa semakin besar selisih antara harga pasar riil dan harga eceran BBM bersubsidi tentunya membebani anggaran negara. Jika tidak diatasi, maka Anggaran Pendapatan Belanja Negara (APBN) akan jebol. Kenaikan bahan pokok juga terjadi disamping naiknya harga BBM tersebut, sehingga menimbulkan masalah baru bagi masyarakat di negara Indonesia terutama dibagian Ekonomi. Namun pemerintah juga tak seharusnya tinggal diam melihat apa yang terjadi di negara ini , mereka terus berupaya mencari langkah untuk menyelesaikan masalah yang terjadi dimasyarakat akibat dari kenaikan BBM tersebut. Dalam masalah ini , qaidah Al-masyaqqoh at-tajlibu al taisir (kesulitan menyebabkan adanya kemudahan atau kesulitan mendatangkan kemudahan) menjadi pertimbangan yang serius bagi pemerintah dalam mengambil keputusan yang tepat untuk menghilangkan kesulitan atau kesusahan yang terjadi dinegara ini dengan melihat hal-hal yang timbul akibat kenaikan harga BBM itu sendiri yang menimbulkan dampak negatif dan positif bagi negara dan masyarakat yang ada didalamnya.Kata kunci: Bahan Bakar Minyak (BBM), Kenaikan bahan pokok , Al-masyaqqoh at-tajlibu al taisir.